Effects of raw iron powder type on the microstructure and properties of Fe–29Ni–17Co Kovar alloys - ZHANG Mei; CHEN Zhipeng; LI Jiaxin; CHEN Wenchao; CHEN Pengqi (Fenmo yejin jishu)
Fe–29Ni–17Co powder mixes were obtained by mixing nickels and cobalt powders, using the reduced iron powders and carbonyl iron powders as the raw materials, respectively, and the sintered Fe–29Ni–17Co Kovar alloy samples were prepared by pressing and sintering at the different temperatures. The effects of the raw iron powder type and sintering temperature on the microstructure and properties of the sintered body were investigated. The results show that the sintered samples prepared by the carbonyl iron powders have the higher relative density and the better comprehensive performance, the relative density of the sintered body sintered at 1250 ℃ is 97.51%, which is about 1.40% higher than that of the sintered body prepared by the reduced iron powders. The hardness and tensile strength of the samples prepared by the carbonyl iron powders reach HRB 84.6 and 533.8 MPa, respectively, and the thermal conductivity, average thermal expansion coefficient (20～400 ℃), and electrical resistivity are 16.45 W·m−1·K−1, 4.71×10−6 K−1, and 0.38 Ω·cm, respectively. The distribution of austenite in the sintered body obtained from the carbonyl iron powders is more uniform, the microstructure stability is better after the low temperature treatment, and the degree of martensitic transformation is lower.